Lumen apposing metal stents are superior to plastic stents in pancreatic walled-off necrosis: a large international multicenter study - Chen, Yen-I; Yang, Juliana; Friedland, Shai; Holmes, Ian; Law, Ryan; Hosmer, Amy; Stevens, Tyler; Franco, Matheus C.; Jang, Sunguk; Pawa, Rishi; Mathur, Nihar; Sejpal, Divyesh V.; Inamdar, Sumant; Trindade, Arvind J.; Nieto, Jose; Berzin, Tyler M.; Sawhney, Mandeep; DeSimone, Michael L.; DiMaio, Christopher; Kumta, Nikhil A.; Gupta, Sanchit; Yachimski, Patrick; Anderloni, Andrea; Baron, Todd H.; James, Theodore W.; Jamil, Laith H.; Ona, Mel A.; Lo, Simon K.; Gaddam, Srinivas; Dollhopf, Markus; Bukhari, Majidah A.; Moran, Robert; Gutierrez, Olaya Brewer; Sanaei, Omid; Fayad, Lea; Ngamruengphong, Saowanee; Kumbhari, Vivek; Singh, Vikesh; Repici, Alessandro; Khashab, Mouen A. (Endoscopy International Open, 2019)
Background and study aims The use of lumen apposing metal stents (LAMS) during EUS-guided transmural drainage (EUS-TD) of pancreatic walled-off necrosis (WON) has gained popularity. Data supporting their use in WON over plastic stents (PS), however, remain scarce. The aim of this study was to compare the clinical efficacy of LAMS (Axios, Boston Scientific) with PS in WON.Patients and methods This was a multicenter, retrospective study involving 14 centers. Consecutive patients who underwent EUS-TD of WON (2012 – 2016) were included. The primary end point was clinical success defined as WON size ≤ 3 cm within a 6-month period without need for percutaneous drainage (PCD) or surgery.Results A total of 189 patients (mean age 55.2 ± 15.6 years, 34.9 % female) were included (102 LAMS and 87 PS). Technical success rates were similar: 100 % in LAMS and 98.9 % in PS (P = 0.28). Clinical success was attained in 80.4 % of LAMS and 57.5 % of PS (P = 0.001). Rate of PCD was similar (13.7 % LAMS vs. 16.3 % PS, P = 0.62), while PS was associated with a greater need for surgery (16.1 % PS vs. 5.6 % LAMS, P = 0.02). Adverse events (AEs) were observed in 9.8 % of LAMS and 10.3 % of PS (P = 0.90) and were rated as severe in 2.0 % and 6.9 %, respectively (P = 0.93). After excluding patients with < 6 months follow-up, the rate of WON recurrence following initial clinical success was greater with PS (22.9 % PS vs. 5.6 % LAMS, P = 0.04).Conclusions When compared to PS, LAMS in WON is associated with higher clinical success, shorter procedure time, lower need for surgery, and lower rate of recurrence.